KARAKTERISTIK GURU IDEAL DALAM KITAB ADABUL ALIM WAL MUTA’ALLIM DAN RLEVANSINYA DENGAN UNDANG-UNDANG GURU DAN DOSEN NO 14 TAHUN 2005 - Muhammad Hanif; Dzulfikar Rodafi; M. Yazid Albasthomi (VICRATINA, 2020)
This research is generally conducted with the aim to describe about: 1) What is the character of ideal teacher in the book Adabul Alim Wal Muta'allim, 2) How is the character of  ideal teacher in the law of teacher and lecturer no. 14, 2005, 3) How is relevance of ideal teacher character in the book Adabul Alim Wal Muta'allim and the law of teacher and lecturer no. 14, 2005. The result of the analysis were obtained by the book Adabul 'Alim Wal Muta'allim contained three characteristics for being an ideal or professional teacher; namely the character of educators towards themselves, the character of educators in learning and teaching, and the character of educators towards students. In the Teacher and Lecturer Law No.14, 2005 which contains four competencies, namely: pedagogical competence, personal competence, social competence and professional competence. While the relevance of the values of both were said to be valid or appropriate. Researcher grouped based on competencies contained in the Law on Teachers and lecturers No. 14, 2005 because it has included all the points of the character of ideal teacher in the book Adabul ‘Alim Wal Muta’allim.